Meso-scale rheological characteristics of foamed bitumen mixtures with high RAP content - Sanchez Melo, Diana B. (2018)
The increasing concerns to reduce the production of harmful emissions, decrease energy consumption and preserve the natural resources have motivated the asphalt industry to lower the production temperatures of asphalt mixtures and incorporate alternative materials. One approach is to use Foamed Bitumen Mixtures (FBM) in combination with Reclaimed Asphalt Pavement (RAP) material. FBMs are composed of a combination of foamed bitumen and mineral aggregates, where unlike conventional HMA where the bitumen is in a liquid state during mixing, the bitumen present in these mixtures is in a foamed state during the mixture’s production. Foamed bitumen production has been mainly based on the techniques developed more than 50 years ago, where the bitumen is heated at high temperatures and then foamed by combining it with cold water, a process that is also known as mechanical foaming. In its foamed state, the bitumen has lower viscosity and expanded volume and can, therefore, be mixed with cold (and often damp) aggregates. These two conditions allow bitumen in its foamed state to coat the aggregates at lower temperatures in comparison to those required in regular HMA materials. More recently, new foaming technologies have been developed as part of Warm Mix Asphalt (WMA) technologies. WMA are asphalt mixtures that are produced at reduced temperatures (i.e. mixing temperatures around 120°C) compared to traditional HMA materials, obtaining mainly environmental and economic benefits. The possibility of reducing the mixing temperature for the asphalt mixture by using these types of foaming technologies is achieved through the use of a series of products and/or processes that act on the bitumen through different mechanisms to provide the adequate workability and coatability conditions when combined with the aggregates at these reduced temperatures. On the other hand, RAP materials are essentially aged asphalt pavements that have reached the end of their service lives and are reclaimed to be used as part of the construction or rehabilitation of pavement structures. The incorporation of this material in Hot Mix Asphalt (HMA) reduces the amount of raw materials added to the final mixtures, which contributes to the conservation of natural resources. Thus, the use of foaming technologies together with the great potential shown by RAP materials to be successfully recycled in asphalt mixtures, are encouraging the use of these materials in road infrastructure projects, thereby requiring the study of their fundamental properties and providing an indication of their expected field performance. This evaluation is particularly important taking into account that a main concern related to the use of lower production temperatures of the mixtures is if the properties of the material are still comparable to those of the traditional HMA. Furthermore, in the case of RAP materials it is still unclear what role the old RAP bitumen plays in the presence of virgin materials, particularly because the blend of RAP-virgin bitumen has a great influence on the final performance of the produced mixtures. Thus, the use of foamed bitumen in mixtures that also include RAP constitutes an important subject of study.